«Invisible hand», organic institutions and spontaneous orders: the evolution of the research programme - Kavaliou, Aliaksandr V. (Journal of the Belarusian State University. Economics, 2024)
The author of the article analyses the genesis and subsequent influence of the Smithian approach of the «invisible hand» as an impersonal force pushing the actions of each economic entity, carried out under the influence of private interest, to achieve the public good. Developing this approach to the mechanism of interpersonal coordination, in the tradition of the Austrian school of economics, the theory of the emergence of organic institutions by K. Menger and the theory of spontaneous order by F. Hayek were created. The basis for explaining the emergence of social institutions and the evolution of humanity as a whole is the interpretation of the emergence and spread of knowledge. A spontaneous order, which arises without a rational plan and will of people, but as a result of their actions, cannot be formed otherwise than by trial and error. The same method touchs the selection of those effective rules that contribute to the formation of social orders. In this regard, it seems misleading to criticise A. Smith for supporting some regulatory government endeavors that can be interpreted as experiments in finding practices that lead to prosperity.
Keywords: «invisible hand»; A. Smith; C. Menger; F. Hayek; knowledge; spontaneous order